ANALYSIS OF LEADERSHIP, PERSONALITY AND WORK ENVIRONMENT ON EMPLOYEE PERFORMANCE IN THE DIRECTORATE OF TRADE ORDER, MINISTRY OF TRADE, WITH JOB SATISFACTION AS A MEDIATION VARIABLE - Bernanda Purba; Nizamuddin (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
The study aims to analyze the influence of leadership, personality, and environment on employee performance with job satisfaction as a mediating variable. This study involved a sample of 141 employees at the Directorate of Trade Order, Ministry of Trade of the Republic of Indonesia. This study uses a quantitative approach, with primary data through questionnaires distributed to respondents, with a Likert scale ranging from 1 to 5. The analysis tool uses a path analysis model with Structural Equation Modeling (SEM) with AMOS-20 software (Analysis of Moment Structure). The research findings indicate that leadership, personality, and environment have a positive and significant effect on employee satisfaction and performance at the Directorate of Trade Order, Ministry of Trade of the Republic of Indonesia. Satisfaction partially mediates the influence of leadership, personality, and environment on employee performance at the Directorate of Trade Order, Ministry of Trade of the Republic of Indonesia.